Conselho da Escola Municipal Adele de Oliveira em CearáMirim/RN: análise de uma experiência de participação na Gestão Escolar Pública - Souza, Ana Paula de (2019)
This work has as study subject the participation experience developed by the counselors of the municipal school Adele de Oliveira’s Scholar Council (SC) from Ceará-Mirim/RN. The discussion was guided by the main theory category, democratic management and participation, with them we analyzed the developed actions by the counselors of the SC of that Potiguar schools, which aim to evaluate how this participation occurs in the process of scholar democratization. In order to substantiate the bibliographic discussion we utilized books and scientific articles bound to the field of educational public policies. Based on Paro (2016); Guedes and Barbalho (2016); Cury (2002); Riscal (2010); Marx (2011), among other authors. Methodologically it was performed bibliographical and documental surveys considering mediations regarding the study object, and we also used interviews in the data collection process with the Scholar Council's constituent members. As theoretical-methodological directive we adopted the dialectic conception to comprehend the object as part of the synthesis effort of diverse determinations that compose the observed reality, perceiving it as a whole inside the capitalist society contradiction movement. In the result analysis, we identified that the Scholar Council harbors the possibility of political-administrative and pedagogical action that amplifies the participation and autonomy in the public school, magnifying the fight for democratization of management at the public state administration scope. Although, we noticed that the change in the scholar management it is gradual, assuming its own rhythm, and could be considered a viable advancement to the teaching institutions in the sense of developing a democratic participative culture, that aims to build in this organizational structure which could turn out to be democratical in the future by means of extension of the legal and practical/deliberative democratic mechanisms; or, in contraposition, could legitimate a verticalized control and authoritarian of the bourgeois state’s maintaining institutions, complying with the capitalist market interests and expanding the excludent social relationships. We observed that the school’s principal election thematic is pointed by the counselors as a potential factor of democratization, because it reveals the opportunity to change a passive political participation of the school community. The council actions, in many moments, reflects a local municipal reality, that still needs advancement regarding to the development of the participative and democratic management, regulated by law. This reality backs up the counselors speech, that signal the need of regulation of the directors election and specific formation to the municipal schools counselors. Also, besides that, this collegiate creation at Ceará-Mirim, contributed to the expansion of the spaces and participation conditions in the scholar context. Finally, we noted through the research that the counselors actions comprehends a plurality of external and internal factors to the researched school, advancements were built with the Scholar Council’s experiences, considering, however, that it is still necessary to overcome challenges to improve the action of the council of the municipal school Adele de Oliveira.